STRENGTHS, WEAKNESSES, OPPORTUNITIES AND CHALLENGES (SWOC) OF ONLINE TEACHING LEARNING AND ASSESSMENT IN A MEDICAL FACULTY - Rajesh PK; Sethuraman KR (Asian Journal of Medicine & Health Sciences, 2020)
Due to COVID-19 pandemic and the movement control order, our faculty had to conduct all the teaching online. The adaptation to online teaching from a traditional face-to-face teaching literally happened overnight. In this paper, we share our initial experiences and our perceptions of the Strengths, Weaknesses, Opportunities and Challenges.